A Review Paper on Assessing an Effective Approach for Adjusting Casting Process Parameters through Optimization - Vimal Kumar; Dr. Lokesh Singh (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Foundries in India are facing lower productivity issues due to low quality of castings produced as well as wrong practices followed, therein. Minimizing rejection as well as production costs is the key area of concern in these foundries. Casting process parameters are important in the optimization of casting process. Design optimization using reliability has also emerged as a promising tool for optimization, using the probabilistic approach. This approach works on probability of failures through various parameters. In this paper we focus on the development of a Markov chain model for investigating the casting failure. In the study, several casting defects and parameters was carried out. This study we proposed a hierarchical model that focuses on the casting failure in industries and accordingly the model was tested for various process parameters.